Paleodietary and Paleoclimatic Reconstruction of Hipparion Fauna at ∼9 Ma From the Xunhua Basin on the Northeastern Tibetan Plateau - Hu, Fei; Song, Bowen; Sun, Yuanyuan; Huang, Wei; Luo, Mansheng; Ji, Junliang; Lin, Qixiang; Algeo, Thomas J.; Zhang, Kexin (Frontiers in Earth Science, 2021)
Stable isotope analysis is pivotal for investigating the paleodiet and paleoecology of ancient mammals. Recently, a ~9-Myr-old Hipparion fauna was discovered at an elevation of ~2200 m above sea level (a.s.l.) in the Xunhua Basin on the northeastern Tibetan Plateau. These fossils can provide key evidence for the ecosystem structure and regional paleoenvironmental reconstruction. Here we present carbon and oxygen isotopic compositions of 56 bulk and 85 serial tooth enamel samples from this fauna, which includes Hipparion platyodus Selve, Chilotherium sp. and Gazella gaudryi Schlosser. The enamel-δ13C values display a wide range of variation ( -11.4‰ to -5.0‰), with a mean value of -8.9±1.0‰, indicating that the fauna consumed mainly C3 plants. However, the heaviest δ13C value of Hipparion (-5.0‰) suggests at least some consumption of C4 plants. Combined with pollen records, we infer that the Hipparion fauna in the Xunhua Basin was living in forest-grassland setting at ~9 Ma. The reconstructed paleo-meteoric δ18O values of the Xunhua Basin at ~9 Ma are lower than the mean annual δ18O of present-day precipitation in this region, suggesting a wetter climate or stronger monsoonal influence than today. Hipparion fauna in the Xunhua Basin yield significantly higher mean values of δ13C and δ18O than contemporary fossils in the Linxia Basin to the east, which is attributed to rapid uplift of the Jishi Shan, blocking water vapor transport by the East Asian Summer Monsoon and making the climate of the Xunhua Basin relatively drier.